Preparation method and application of concave octahedral MoOx / UiO-66 composite material
By conducting hydrothermal reaction under specific conditions, a stable concave octahedral MoOx/UiO-66 composite material was prepared, which solved the problems of unstable concave structure and complex process of non-precious metal catalysts, and achieved a significant improvement in catalytic reaction activity.
Patent Information
- Application Number
- CN202311158032.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-09-08
AI Technical Summary
In the prior art, the concave structure of the preparation of non-precious metal catalysts is unstable, the process is complex, and it is difficult to achieve nanomaterials with controllable morphology and stable structure.
UiO-66 is used as the raw material and Na2MoO4 aqueous solution as the solvent to prepare concave octahedral MoOx/UiO-66 composite material through hydrothermal reaction under specific temperature and pH conditions. MoO2-4 is used as an oxidant to crack the organic ligand under acidic conditions, and introduce active metal center MoOx nanoparticles.
The stable preparation of concave octahedral MoOx/UiO-66 composite material has been achieved, with active concave surfaces, transition metal active sites and highly accessible inner and outer surfaces, significantly improving catalytic reaction activity.
Smart Images

Figure CN117160541B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of nano material preparation, and particularly relates to a concave octahedral MoO x Preparation method and application of / UiO-66 composite material. Background Art
[0002] For a long time, people have been committed to developing new catalysts to alleviate the energy crisis and solve environmental problems. The physical and chemical properties of catalysts depend not only on their chemical composition, but also on the material morphology and surface chemical properties. Controlling the morphology of catalysts plays a key role in enhancing the mass transfer of interfacial chemical reactions and improving the surface area and pore utilization. Like eaves structures, nanospheres and nanotubes, the active sites of these catalysts are dispersed on the curved surface, and the curved surface structure can expose more active sites and increase the ion diffusion rate. Therefore, preparing catalysts with unique morphology has been proven to be an effective method to improve the performance of catalytic reactions.
[0003] Metal-organic frameworks (MOFs) are a class of highly ordered porous crystalline materials formed by the coordination of metal ions / clusters with organic ligands. Due to their advantages such as high surface area, high porosity, diverse structures, controllable morphology and size, and easy functionalization, MOFs have attracted great attention in recent decades and have shown great application potential in chemistry and materials science, such as in catalysis, sensors, gas adsorption and separation, batteries, biomedicine, and drug delivery. Currently, MOFs are considered to be universal templates for the preparation of various metal compounds with unique morphologies and structures.
[0004] Among various morphologies, nanoparticles with concave shapes represent a new class of catalysts with good stability and catalytic activity. Unlike common convex structures, concave nanoparticles have highly accessible inner and outer regions that can expose more active surfaces. At the same time, the high density of low-coordinated atoms on the surface of these particles provides abundant highly active catalytic sites. Concave nanoparticles are usually synthesized at the mesoscale (tens to hundreds of nanometers), and they can be used as highly stable heterogeneous catalysts due to their low solubility and good dispersibility. However, since the concave nanoparticles expose a large number of high-energy surfaces of low-coordinated step atoms, it is thermodynamically unfavorable for the synthesis of concave nanoparticles, which requires precise control of kinetics during the nanoparticle synthesis process. Although rapid progress has been made in controlling the morphology and structure of catalysts, most of the current research focuses on noble metal materials. Therefore, it is still a challenge to construct non-noble metal nanomaterials with controllable morphology and stable structure by simple means. Summary of the invention
[0005] In order to solve the above problems existing in the prior art, the present invention provides a concave octahedral MoOx The preparation method of the composite material of UiO-66 is to use UiO-66 as raw material and Na2MoO4 aqueous solution as solvent, and to prepare MoO with concave octahedral structure by hydrothermal reaction under specific temperature and pH conditions. x In the composite material of UiO-66, MoO2-4, as an oxidant, can selectively cleave the organic ligand into small molecular fragments under acidic conditions, generate coordinated unsaturated zirconium atoms, and introduce active metal centers into MoO x The method has the advantages of easy reaction control, low-cost raw materials, simple process, and easy manipulation, and solves the problems of complex preparation process, unstable concave structure, and easy collapse in the prior art. The concave octahedral MoO x The / UiO-66 composite material has good structural stability, active concave surfaces of coordinated unsaturated atoms, transition metal active sites, and highly accessible internal and external surfaces, showing good application prospects for improving catalytic reaction activity.
[0006] The present invention adopts the following technical solution:
[0007] A concave octahedral MoO x A method for preparing a UiO-66 composite material comprises the following steps:
[0008] (1) Synthesis of UiO-66 precursor by a classical hydrothermal method;
[0009] (2) Add UiO-66 to a Na2MoO4 solution at pH = 5 and ultrasonicate until a uniformly dispersed reaction precursor solution is formed;
[0010] (3) transferring the reaction precursor solution to a stainless steel autoclave lined with polytetrafluoroethylene and performing a hydrothermal reaction in a drying oven;
[0011] (4) After the reaction is completed, the mixture is cooled to room temperature, centrifuged, washed, and dried until the water is completely evaporated to obtain a white solid powder MoO x / UiO-66 nanocomposite materials.
[0012] Furthermore, the UiO-66 is used in an amount of 100 mg.
[0013] Furthermore, the concentration of the Na2MoO4 solution is 0.01 mol / L and the dosage is 70 mL.
[0014] Furthermore, the specific preparation method of the Na2MoO4 solution with a pH of 5 is as follows: adding 0.1 mol / L H2SO4 solution dropwise into the Na2MoO4 solution, and measuring the pH of the solution in real time with a pH meter until the pH is 5.
[0015] Furthermore, the hydrothermal reaction is specifically: hydrothermal reaction at 180°C for 6 hours.
[0016] Furthermore, the washing solvent is deionized water, and the washing times are 3 times.
[0017] Furthermore, the drying method is vacuum drying at 60°C for 12 hours.
[0018] Furthermore, the concave octahedral MoO x / UiO-66 composite materials were used as catalysts for Fenton-like catalytic reactions.
[0019] The beneficial effects of the present invention are:
[0020] (1) MoO of the present invention x The / UiO-66 composite material has a concave octahedral structure with a stable structure, which avoids the problem of easy structural collapse during the synthesis of the concave structure.
[0021] (2) MoO of the present invention x The preparation method of the / UiO-66 composite material has the advantages of easy reaction control, low raw material cost, simple process, easy manipulation, etc., which solves the problem of complex preparation process in the prior art.
[0022] (3) MoO of the present invention x The / UiO-66 composite material has an active concave surface of coordinated unsaturated atoms, transition metal active sites, and highly accessible internal and external surfaces, showing good application prospects for improving catalytic reaction activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The octahedral UiO-66 and concave octahedral MoO prepared in Example 1 are x XRD pattern of / UiO-66 composite material;
[0024] Figure 2 (a), (b) and (c), (d) correspond to the octahedral UiO-66 and concave octahedral MoO prepared in Example 1, respectively. x SEM image of / UiO-66 composite material;
[0025] Figure 3 The concave octahedral MoO prepared in Example 1 x TEM image of / UiO-66 composite material;
[0026] Figure 4 The concave octahedral MoO prepared in Example 1 x HRTEM image of / UiO-66 composite material;
[0027] Figure 5 The concave octahedral MoO prepared in Example 1 x XPS graph of / UiO-66 composite material;
[0028] Figure 6 (ad) is a SEM image, (eh) is a HAADF-STEM image, and the bar graph inset is the ICP test result of the Zr and Mo element contents. (a), (e) and (d), (h) correspond to the UiO-66 precursor and the concave octahedral MoO in Example 1, respectively. x SEM and HAADF-STEM of the / UiO-66 composite material, (b), (f) and (c), (g) correspond to the SEM and HAADF-STEM of the samples in Example 2 and Example 3, respectively;
[0029] Figure 7 is the SEM of the sample in Example 4;
[0030] Figure 8 is the SEM of the sample in Example 5;
[0031] Fig. 9 is the SEM of the sample in Comparative Example 1;
[0032] Fig.10 is the SEM of the sample in Comparative Example 2;
[0033] Fig.11 The octahedral UiO-66 and concave octahedral MoO prepared in Example 1 are x / Comparison of the catalytic degradation performance of ciprofloxacin between UiO-66 and commercial MoO3;
[0034] Fig.12 The concave octahedral MoO with different surface depression degrees prepared in Example 1, Example 2 and Example 3 are x / Comparison of the performance of UiO-66 composite materials in catalytic degradation of ciprofloxacin;
[0035] Fig.13 The concave octahedral MoO prepared in Example 1 x Performance diagram of the cyclic test of / UiO-66 composite material. DETAILED DESCRIPTION
[0036] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings, i.e., embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined as long as they do not conflict with each other.
[0037] Example 1
[0038] This embodiment provides a concave octahedral MoO x The preparation method of the UiO-66 composite material, the specific experimental steps are as follows:
[0039] (1) Synthesis of UiO-66 precursor by a classical hydrothermal method;
[0040] (2) Use 0.1 mol / L H2SO4 solution to adjust the pH of 0.01 mol / L Na2MoO4 solution to 5, add 100 mg UiO-66 to 70 mL of the above solution, and sonicate to form a uniformly dispersed reaction precursor solution;
[0041] (3) The reaction precursor solution was transferred to a stainless steel autoclave lined with polytetrafluoroethylene and subjected to a hydrothermal reaction at 180 °C in a drying oven for 6 h. After the reaction was completed, the solution was cooled to room temperature.
[0042] (4) The obtained MoO x The / UiO-66 composite material was washed three times by centrifugation with deionized water and then dried in vacuum at 60 °C to obtain MoO with a concave octahedral morphology. x / UiO-66 composite material.
[0043] In this embodiment, the prepared concave octahedral MoO x The / UiO-66 composite material was subjected to XRD, SEM, TEM, HRTEM and XPS analysis, and the results are as follows:
[0044] XRD results are as follows Figure 1 As shown, the prepared concave octahedral MoO x The / UiO-66 composite material still has the same diffraction peaks as the original UiO-66 and is consistent with the standard UiO-66 card, indicating that the high-temperature hydrothermal reaction did not completely destroy the structure of UiO-66. x / UiO-66 still maintains the crystalline structure of UiO-66. SEM results at different magnifications are as follows Figure 2 As shown in (a) and (b), the prepared UiO-66 has a smooth octahedral morphology, an average particle size between 500-800 nm, and good dispersion. Figure 2 As can be seen in (c) and (d), MoO obtained by hydrothermal treatment in acidic Na2MoO4 solution x Each face of / UiO-66 has obvious deep depression and the surface becomes rough. Although the reaction is carried out under high temperature hydrothermal conditions, the product structure does not collapse and still maintains the original octahedral configuration, indicating that the concave octahedral MoOx / UiO-66 composite materials have good structural stability. Figure 3 (a) and (b) are TEM images at different magnifications. x / UiO-66 presents a hollow structure with highly accessible inner and outer areas, which helps to expose more active surfaces. Figure 4 It can be seen from the HRTEM image that the concave octahedral MoO x / UiO-66 also contains MoO3 particles and a small amount of Mo 4+ ( Figure 5 ), multivalent molybdenum oxides can provide abundant active sites for catalytic reactions.
[0045] Example 2
[0046] This embodiment provides a concave octahedral MoO x A method for preparing a / UiO-66 composite material is basically the same as the preparation method in Example 1, except that the hydrothermal reaction time is 0.5 h.
[0047] like Figure 6 As shown in (b) and (f), MoO x Preparation method of MoO / UiO-66 composite material, the final prepared MoO x The / UiO-66 composite material showed an octahedron with a slight depression on the surface, indicating that the reaction had begun at 0.5 h.
[0048] Example 3
[0049] This embodiment provides a concave octahedral MoO x A method for preparing a / UiO-66 composite material is basically the same as the preparation method in Example 1, except that the hydrothermal reaction time is 2 h.
[0050] like Figure 6 As shown in (c) and (g), MoO x Preparation method of MoO / UiO-66 composite material, the final prepared MoO x The / UiO-66 composite material showed an octahedron with a partially depressed surface, which indicated that the reaction was not complete at 2 h and the surface of the material was not completely depressed.
[0051] Example 4
[0052] This embodiment provides a concave octahedral MoO xA method for preparing a / UiO-66 composite material is basically the same as the preparation method in Example 1, except that the amount of H2SO4 solution added is adjusted to a pH value of 2 in the reaction precursor solution.
[0053] like Figure 7 As shown, MoO x / UiO-66 composite material preparation method, the final product surface has triangular flake material peeled off. This shows that when pH=2, the acidity is too strong, the reaction is directly carried out on the UiO-66 surface, and no surface depression occurs.
[0054] Example 5
[0055] This embodiment provides a concave octahedral MoO x A method for preparing a / UiO-66 composite material is basically the same as the preparation method in Example 1, except that the amount of H2SO4 solution added is adjusted to a pH value of 6 in the reaction precursor solution.
[0056] like Figure 8 As shown, MoO x The preparation method of the composite material of MgO / UiO-66 was studied, and the final product still maintained the original planar octahedral structure of UiO-66. This shows that when pH=6, the reaction conditions are too mild and UiO-66 will not sink.
[0057] Comparative Example 1
[0058] This embodiment provides a concave octahedral MoO x A method for preparing a / UiO-66 composite material is basically the same as the preparation method in Example 1, except that the reaction precursor liquid is deionized water with a pH value of 5.
[0059] like Fig. 9 As shown, the MoO x The method for preparing the composite material of H2SO4 / UiO-66 is shown in Figure 1. The final product still retains the original planar octahedral structure of UiO-66, indicating that UiO-66 will not sag when only H2SO4 exists.
[0060] Comparative Example 2
[0061] This embodiment provides a concave octahedral MoO x A method for preparing a / UiO-66 composite material is basically the same as the preparation method in Example 1, except that the reaction precursor solution is a Na2MoO4 solution without adding any acid to adjust the pH.
[0062] like Fig.10 As shown, the MoO xThe surface of the final product was slightly concave, indicating that UiO-66 can be concave when only Na2MoO4 exists.
[0063] From Examples 1 to 5 and Comparative Examples 1 to 2, the following conclusions can be drawn:
[0064] (1) It can be seen from Example 1, Example 2 and Example 3 that:
[0065] It can be seen from Examples 1, 2 and 3 that as the reaction time increases, the surface of the UiO-66 octahedron gradually becomes concave, and when the reaction time reaches 6 h, the degree of concave reaches the maximum, indicating that the hydrothermal reaction of 6 h in Example 1 is the most suitable reaction time for generating concave octahedrons. The ICP test results also show that during the hydrothermal reaction, the relative contents of the Zr element and the Mo element remain substantially constant, so the influence of the element content can be ignored in the catalytic performance test.
[0066] (2) It can be seen from Example 1, Example 4 and Example 5 that:
[0067] Adjusting the reaction precursor solution pH to 2 or 6 cannot cause the material surface to be completely concave, indicating that concave octahedrons can only be generated when the reaction precursor solution pH is 5 in Example 1.
[0068] (3) It can be seen from Example 1, Comparative Example 1 and Comparative Example 2 that:
[0069] In Comparative Example 1, the reaction precursor solution was deionized water with a pH of 5, and no depression occurred on the surface of the material, indicating that the acidic condition was not the cause of the depression of the material. In Comparative Example 2, the reaction precursor solution was a Na2MoO4 solution without adding any acid to adjust the pH, and depression occurred on the surface of some materials, but the degree of depression was low, indicating that Na2MoO4 is a necessary condition for the occurrence of depression. In Example 1, the pH of the Na2MoO4 solution was adjusted to 5 with H2SO4, and a general deep depression occurred on the surface of the material, indicating that the presence of H2SO4 enhanced the oxidizability of Na2MoO4, thereby cracking the organic ligands inside UiO-66, causing it to be depressed.
[0070] Catalytic performance test
[0071] All Fenton-like catalytic experiments were conducted in a 100 mL reactor at room temperature (25 ± 2 °C), containing 40 mL of a 10 ppm ciprofloxacin solution. In a typical Fenton-like catalytic experiment, 10 mg of the catalyst prepared in Example 1 (or Example 2 or Example 3) was added to 40 mL of CIP solution and pre-adsorbed by stirring; after reaching adsorption equilibrium, the pH of the reaction system was adjusted to 11 with 0.1 mol / L NaOH solution; then, 6 mg of persulfate (PMS) was added to the above solution and stirred. At certain intervals, the upper layer of liquid was extracted and the chemical composition of the filtered liquid was immediately studied using a UV-visible spectrophotometer. All experiments were repeated three times and the average data are given.
[0072] The octahedral UiO-66 and concave octahedral MoO prepared in Example 1 were x The catalytic degradation performance of ciprofloxacin was tested on / UiO-66 and compared with that of commercial MoO3. Fig.11 As shown in the figure, the catalytic reaction results show that all three have a certain adsorption effect on ciprofloxacin, among which the concave octahedral MoO x / UiO-66 has a stronger adsorption effect on ciprofloxacin, which is more conducive to the interaction between the catalyst and the reactant molecules. The results of catalytic degradation experiments also show that commercial MoO3 and octahedral UiO-66 have almost no effect on the degradation of ciprofloxacin, but UiO-66 has a significant adsorption effect on ciprofloxacin, while concave octahedral MoO x After adsorbing ciprofloxacin, / UiO-66 can still achieve catalytic degradation of pollutants within 10 min, with a degradation rate of 96%, indicating that the MoO with concave structure x / UiO-66 can significantly improve the catalytic reaction performance.
[0073] Similarly, the concave octahedral MoO with different surface depression degrees obtained by controlling the reaction time in Example 1, Example 2 and Example 3 were x / UiO-66 was tested for its catalytic performance. Fig.12 As shown in FIG. 1 , the catalytic degradation efficiency increases with the increase of the surface depression degree, and the adsorption of pollutants is also enhanced to a certain extent. Among them, the MoO x / UiO-66 has the best catalytic degradation performance, which shows that the depressions on the material surface have an important influence on the catalytic performance. The greater the depressions on the material surface, the better the catalytic performance. Fig.13 The concave octahedral MoO prepared in Example 1 x / UiO-66 performance diagram during cyclic reaction. As can be seen from the figure, after 4 cycles, the concave octahedral MoOx The performance of / UiO-66 did not decrease significantly, proving that it has good reaction stability.
[0074] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A concave octahedral MoO x / The preparation method of UiO-66 composite material is characterized by: The following steps are involved: (1) Add UiO-66 to Na2MoO4 solution with pH = 5 and ultrasonicate until a uniformly dispersed reaction precursor solution is formed; (2) transferring the reaction precursor solution to a polytetrafluoroethylene-lined stainless steel autoclave and performing a hydrothermal reaction in a drying oven; (3) After the reaction is completed, the mixture is cooled to room temperature, centrifuged, washed, and dried until the water is completely evaporated to obtain a white solid powder MoO x / UiO-66 nanocomposite; The specific preparation method of the Na2MoO4 solution with a pH of 5 described in step (1) is as follows: 0.1 mol / L H2SO4 solution is added dropwise to the Na2MoO4 solution, and the pH of the solution is measured in real time with a pH meter until the pH is 5.
2. The concave octahedral MoO according to claim 1 x / The preparation method of UiO-66 composite material is characterized by: The amount of UiO-66 used in step (1) is 100 mg.
3. The concave octahedral MoO according to claim 1 x / The preparation method of UiO-66 composite material is characterized by: The Na2MoO4 solution described in step (1) has a concentration of 0.01 mol / L and is used in an amount of 70 mL.
4. The concave octahedral MoO according to claim 1 x / The preparation method of UiO-66 composite material is characterized by: The hydrothermal reaction in step (2) is specifically: hydrothermal reaction at 180° C. for 6 h.
5. The concave octahedral MoO according to claim 1 x / The preparation method of UiO-66 composite material is characterized by: The washing solvent in step (3) is deionized water, and the washing times are 3 times.
6. The concave octahedral MoO according to claim 1 x / The preparation method of UiO-66 composite material is characterized by: The drying method described in step (3) is vacuum drying at 60°C for 12 h.
7. A concave octahedral MoO prepared by the preparation method according to any one of claims 1 to 6 x / UiO-66 composite material.
8. The concave octahedral MoO as claimed in claim 7 x / UiO-66 composite materials were used as catalysts for Fenton-like catalytic reactions.
Citation Information
Patent Citations
Zirconium-based metal organic frameworks UiO-66 and application thereof
CN108854967A
Concave-octahedron-shaped PtCuNi alloy nanoparticles and a preparation method thereof
CN110212206A